Simplified calculation of vibrations in shell and tube heat exchangers with liquids (2014)
A very serious problem to consider in the mechanical design of Shell and Tube Heat Exchangers is the vibrations induced in the tubes by the fluid pass. The vibration of the tubes of the Shell and Tube Heat Exchangers is a factor that limits the operation of these equipments in important way. The dynamic processes of the nonstationary fluids that happen during the flow produce vibrations. These are turbulent pulsations of the pressure (turbulent flow), initiation of the vortex and separation of the tubes during the crossing of the currents, hydro elastic interaction of the assemblies of the transmitting elements of the heat (tubes) with the flow, and acoustic phenomena. In the present work the procedure for the calculation of the vibrations in Shell and Tube Heat Exchangers is described.